Management and paradigm influence: A call for paradigm shift - Amellah, Saif; Foulad, Rida; Jebli, Samir; Sahib , Amal-Oudiî; Bouaziz, Abdelhak (Edelweiss Applied Science and Technology, 2024)
This article critically examines the influence of the dominant paradigm in management, characterized by its emphasis on profit maximization and individualism, which has resulted in profound socio-economic and environmental challenges. The methodology involves an exploration of the historical evolution of management practices and an analysis of how these practices have primarily served shareholder interests while often neglecting broader impacts on employees, customers, and society. The results of this examination highlight the need for a paradigm shift that prioritizes ethical considerations, social responsibility, and sustainability in management decision-making processes. By advocating for this shift, this article encourages organizations to realign their objectives to balance financial performance with the goal of serving humanity more effectively. The conclusion emphasizes that this reorientation not only addresses contemporary management challenges but also fosters long-term sustainable success. Ultimately, this article’s significant contribution lies in its call to elevate human values in management decisions, thereby creating business models that positively impact society as a whole.